Carbon nanotube-polyetherimide grafted carbon fiber / nylon composite material as well as preparation method and application thereof

By grafting polyetherimide onto the surface of carbon fibers and reacting it with acidified carbon nanotubes, a carbon nanotube-polyetherimide grafted carbon fiber and nylon blend is formed, which solves the problem of poor compatibility between carbon fibers and nylon matrix, significantly improves the mechanical properties of composite materials, and is suitable for the external pressure reinforcement layer of marine flexible pipes.

CN121045816APending Publication Date: 2025-12-02CHINA PETROLEUM PIPELINE ENG CO LTD +2
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202511612972.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-06
Publication Date
2025-12-02

AI Technical Summary

Technical Problem

The existing carbon fiber and nylon matrix have poor compatibility and weak interfacial bonding, resulting in insufficient mechanical properties of nylon composite materials, which makes it difficult to meet the requirements of the external pressure reinforcement layer of marine flexible pipes.

Method used

By grafting polyetherimide onto the surface of carbon fibers and reacting it with acidified carbon nanotubes to form carbon nanotube-polyetherimide grafted carbon fibers, the carbon nanotubes are then melt-blended with nylon resin to achieve uniform dispersion and reinforcement of carbon nanotubes on the carbon fiber surface.

Benefits of technology

It significantly improves the mechanical properties of composite materials, enhances the interfacial bonding strength and compatibility between carbon fibers and nylon matrix, solves the problem of uniform dispersion of carbon nanotubes in nylon matrix, and enhances the overall performance of composite materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121045816A_ABST
    Figure CN121045816A_ABST
Patent Text Reader

Abstract

The invention provides a carbon nanotube-polyetherimide grafted carbon fiber / nylon composite material as well as a preparation method and application thereof, and belongs to the technical field of composite materials. The preparation method comprises the following steps: mixing polyetherimide, a condensing agent, acidified carbon fibers and an organic solvent, and carrying out first amidation reaction to obtain polyetherimide grafted carbon fibers; mixing the polyetherimide grafted carbon fibers, a condensing agent, acidified carbon nanotubes and an organic solvent, and carrying out a second amidation reaction to obtain carbon nanotube-polyetherimide grafted carbon fibers; the carbon nanotube-polyetherimide grafted carbon fibers and nylon resin are subjected to melt blending to obtain the carbon nanotube-polyetherimide grafted carbon fiber / nylon composite material, so that the carbon nanotubes are uniformly dispersed on the surfaces of the carbon fibers, the reinforcing effect of the carbon nanotubes is fully exerted, the nanoscale roughness of the surfaces of the carbon fibers is also increased, and the carbon nanotube-polyetherimide grafted carbon fiber / nylon composite material is prepared. The multi-level reinforcement from micron level to nano level is realized, and the mechanical property of the composite material is obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure belongs to the field of composite material technology, specifically relating to a carbon nanotube-polyetherimide grafted carbon fiber / nylon composite material, its preparation method, and its application. Background Technology

[0002] Nylon, scientifically known as polyamide (PA), is an important engineering plastic with excellent comprehensive properties and is widely used in automotive manufacturing, electronics, aerospace, and other fields. Nylon composites refer to composite materials with nylon as the matrix material, enhanced by introducing fillers. Carbon fiber (CF) possesses extremely high strength and modulus; when added as a filler to the nylon matrix, it can improve the mechanical properties of the composite material. However, due to the smooth surface of carbon fiber, its poor compatibility with the nylon matrix and weak interfacial bonding force make it difficult to achieve excellent reinforcement effects.

[0003] To improve the compatibility between carbon fiber and nylon matrix, carbon fiber modification is usually required. Current modification methods mainly fall into three categories: surface oxidation, surface coating, and surface grafting. However, current modification methods have limited effectiveness in improving the compatibility between carbon fiber and nylon matrix, and the mechanical properties of the resulting nylon composite materials remain difficult to improve.

[0004] Marine flexible pipelines are crucial equipment for offshore oil and gas development, transporting various fluids in the marine environment and offering unique advantages over traditional rigid pipelines. The external pressure reinforcement layer is a vital structural layer in marine flexible pipelines, distributing external pressure evenly to other layers, enabling the entire pipeline system to collaboratively withstand various loads and improving overall pipeline performance and reliability. The external pressure reinforcement layer requires high mechanical properties to ensure pipeline integrity and safety. Current carbon fiber-nylon composite materials have relatively poor mechanical properties, making it difficult to meet the requirements of the external pressure reinforcement layer in marine flexible pipelines. Summary of the Invention

[0005] This disclosure aims to at least solve one of the technical problems existing in the prior art, and to provide a carbon nanotube-polyetherimide grafted carbon fiber / nylon composite material, its preparation method, and its application.

[0006] One aspect of this disclosure provides a method for preparing a carbon nanotube-polyetherimide grafted carbon fiber / nylon composite material, the method comprising: Polyetherimide, condensing agent, acidified carbon fiber and organic solvent are mixed and subjected to a first amidation reaction to obtain polyetherimide grafted carbon fiber; The polyetherimide-grafted carbon fibers, condensing agent, acidified carbon nanotubes and organic solvent are mixed and subjected to a second amidation reaction to obtain carbon nanotube-polyetherimide-grafted carbon fibers. The carbon nanotube-polyetherimide grafted carbon fiber and nylon resin are melt-blended to obtain a carbon nanotube-polyetherimide grafted carbon fiber / nylon composite material. Optionally, the acidified carbon fiber is formed using the following method: Carbon fibers are mixed with nitric acid and then acidified to obtain acidified carbon fibers; wherein... The acidification treatment was carried out at a temperature of 80°C for 2 hours.

[0007] Optionally, in the first amidation reaction, the ratio of condensing agent to organic solvent is 5 mg: 100 mL, the mass ratio of polyetherimide to acidified carbon fiber is 1 g: 5 g, and the ratio of polyetherimide to organic solvent is 1 g: 100 mL. The temperature of the first amidation reaction was 100℃, and the reaction time was 12h.

[0008] Optionally, the acidified carbon nanotubes are formed using the following method: Carbon nanotubes are mixed with a sulfuric acid-nitric acid mixture and then acidified to obtain acidified carbon nanotubes; among which... The ratio of carbon nanotubes to sulfuric acid-nitric acid mixture is 4g:280mL; The acidification treatment was carried out at a temperature of 80°C for 3 hours.

[0009] Optionally, in the second amidation reaction, the ratio of condensing agent to organic solvent is 10 mg: 100 mL, the mass ratio of polyetherimide grafted carbon fiber to acidified carbon nanotube is 5 g: 5 g, and the ratio of acidified carbon nanotube to organic solvent is 5 g: 100 mL. The second amidation reaction was carried out at 100°C for 12 hours.

[0010] Optionally, the condensing agent is 2-(7-azabenzotriazole)-N,N,N',N'-tetramethylurea hexafluorophosphate; The weight-average molecular weight of the polyetherimide is 1000~2000; The nylon resin is nylon 6.

[0011] Optionally, the melt blending temperature is 235°C, the rotor speed is 40 rpm, and the time is 4 min.

[0012] Optionally, the mass fraction of carbon nanotube-polyetherimide grafted carbon fiber in the carbon nanotube-polyetherimide grafted carbon fiber / nylon composite material is 1wt%~7wt%.

[0013] In another aspect of this disclosure, a carbon nanotube-polyetherimide grafted carbon fiber / nylon composite material is provided, wherein the carbon nanotube-polyetherimide grafted carbon fiber / nylon composite material is prepared by the preparation method described above.

[0014] In another aspect of this disclosure, an application of a carbon nanotube-polyetherimide grafted carbon fiber / nylon composite material is proposed, wherein the carbon nanotube-polyetherimide grafted carbon fiber / nylon composite material described above is applied to a marine flexible pipe.

[0015] This disclosure presents a carbon nanotube-polyetherimide grafted carbon fiber / nylon composite material, its preparation method, and its applications. The preparation method of this carbon nanotube-polyetherimide grafted carbon fiber / nylon composite material includes: mixing polyetherimide, a condensing agent, acidified carbon fiber, and an organic solvent to perform a first amidation reaction to obtain polyetherimide grafted carbon fiber; mixing the polyetherimide grafted carbon fiber, the condensing agent, the acidified carbon nanotube, and the organic solvent to perform a second amidation reaction to obtain carbon nanotube-polyetherimide grafted carbon fiber; and melt-blending the carbon nanotube-polyetherimide grafted carbon fiber and nylon resin to obtain the carbon nanotube-polyetherimide grafted carbon fiber / nylon composite material. This disclosure uniformly grafts carbon nanotubes onto the surface of carbon fibers, which not only achieves uniform dispersion of carbon nanotubes on the carbon fiber surface and fully utilizes the reinforcing effect of carbon nanotubes, but also increases the nanoscale roughness of the carbon fiber surface, realizing multi-level reinforcement from the micrometer to the nanometer scale, significantly improving the mechanical properties of the composite material, solving the problem of the difficulty in uniformly dispersing carbon nanotubes in the nylon matrix, avoiding the agglomeration of carbon nanotubes, and fully utilizing the reinforcing effect of carbon nanotubes. Attached Figure Description

[0016] Figure 1 This is a flowchart illustrating the preparation method of carbon nanotube-polyetherimide grafted carbon fiber / nylon composite material according to a specific embodiment of this disclosure. Figure 2 This is a schematic diagram of the reaction process of polyetherimide and acidified carbon fiber according to a specific embodiment of this disclosure. Figure 3 This is a scanning electron microscope (SEM) image of the unmodified carbon fiber surface in Embodiment 1 of this disclosure, wherein, Figure 3 (a) is a 50 μm scale bar. Figure 3 (b) is a 5μm scale; Figure 4 This is a scanning electron microscope (SEM) image of the surface of carbon nanotube-polyetherimide grafted carbon fiber in Example 1 of this disclosure; wherein, Figure 4 (a) is a 50 μm scale bar. Figure 4 (b) is a 5μm scale; Figure 5This is a schematic diagram of the reaction process of KH550 and acidified carbon fiber in Comparative Example 3 of this disclosure. Detailed Implementation

[0017] To enable those skilled in the art to better understand the technical solutions of this disclosure, the disclosure will be further described in detail below with reference to the accompanying drawings and specific embodiments. It should be understood that the specific embodiments described herein are only used to explain this disclosure and represent a part of the embodiments of this disclosure, not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of this disclosure without creative effort are within the protection scope of this disclosure.

[0018] As shown in Figure 1, one aspect of this disclosure provides a method S100 for preparing carbon nanotube-polyetherimide grafted carbon fiber / nylon composite material, specifically including the following steps S110~S130: S110. Polyetherimide, condensing agent, acidified carbon fiber and organic solvent are mixed and subjected to the first amidation reaction to obtain polyetherimide grafted carbon fiber.

[0019] In step S110, the acidified carbon fiber is formed by mixing carbon fiber and nitric acid and then acidifying the mixture (referred to as the first acidification treatment) to obtain acidified carbon fiber; wherein the acidification treatment temperature of the carbon fiber is 70~90℃ and the time is 1~3h, for example, 80℃ and 2h are more preferred.

[0020] It should be noted that the length of the carbon fiber used in the above carbon fiber acidification process is preferably 4~8mm, and more preferably 6mm.

[0021] It should also be noted that concentrated nitric acid, such as commercially available 68wt% concentrated nitric acid, is preferred in the above-mentioned carbon fiber acidification process. It is easy to understand that this embodiment does not have special requirements on the amount of nitric acid used in the acidification process; it is sufficient to immerse the carbon fiber.

[0022] It should be noted that the preferred ratio of carbon fiber to concentrated nitric acid used in the above-mentioned carbon fiber acidification treatment is 3g:50mL, and the carbon fiber acidification treatment is preferably carried out under the conditions of water bath heating, condensation reflux and mechanical stirring.

[0023] It should be noted that the carbon fibers can preferably be pretreated before acidification, for example, by washing with acetone. Furthermore, after the carbon fiber acidification is completed, the resulting acidified solution can preferably be cooled to room temperature, diluted with deionized water, then vacuum filtered and washed until the pH of the filtrate is 6.5-7.5, preferably 7, and then dried to obtain the acidified carbon fibers; wherein the drying temperature is preferably 80°C, and the drying time is preferably 10 hours.

[0024] In step S110, the weight-average molecular weight of polyetherimide (PEI) is 1000-2000, and its structural formula is as follows: Figure 2 As shown, m and n in the structural formula represent the number of two main repeating units, and the values ​​of m and n range from 15 to 25, more preferably 1800.

[0025] In step S110, the condensing agent used in the first amidation reaction is 2-(7-azabenzotriazole)-N,N,N',N'-tetramethylurea hexafluorophosphate (HATU). The organic solvent used in the first amidation reaction is preferably dimethylformamide (DMF), specifically anhydrous DMF.

[0026] Further, in the first amidation reaction of step S110, the ratio of condensing agent to organic solvent is 5 mg:100 mL. Secondly, the mass ratio of polyetherimide to acidified carbon fiber is 1:2 to 10, more preferably 1:5. The ratio of polyetherimide to organic solvent is 1 to 5 g:100 mL, more preferably 1 g:100 mL.

[0027] Further, in step S110, the temperature of the first amidation reaction is preferably 100~120°C, and the reaction time is 8~12h. For example, the temperature is further preferably 100°C, and the time is further preferably 12h. The first amidation reaction is preferably carried out under oil bath conditions.

[0028] It should be noted that the mixing order of the components in step S110 is not specifically limited. For example, it is preferable to first dissolve the polyetherimide in an organic solvent to obtain a polyetherimide solution, and then add the condensing agent and acidified carbon fiber to the polyetherimide solution. After mixing evenly, the mixture is heated to carry out the first amidation reaction. During the first amidation reaction, the amino groups on the surface of the polyetherimide and the carboxyl groups on the surface of the acidified carbon fiber react, thereby grafting the polyetherimide onto the carbon fiber surface. The reaction process of the polyetherimide and the acidified carbon fiber is as follows: Figure 2 As shown.

[0029] It should be further noted that, after the first amidation reaction is completed, this embodiment preferably cools the resulting reaction solution and washes it with acetone to remove excess organic solvent, then washes the resulting solid product with water and dries it to obtain polyetherimide grafted carbon fiber; the drying temperature is preferably 80°C and the drying time is preferably 10 hours.

[0030] S120. The polyetherimide-grafted carbon fiber, condensing agent, acidified carbon nanotubes and organic solvent are mixed to carry out a second amidation reaction to obtain carbon nanotube-polyetherimide-grafted carbon fiber.

[0031] In step S120, the acidified carbon nanotubes are formed by the following method: carbon nanotubes are mixed with sulfuric acid-nitric acid mixture and then subjected to acidification treatment (referred to as the second acidification treatment) to obtain acidified carbon nanotubes; wherein, the ratio of carbon nanotubes to sulfuric acid-nitric acid mixture is 3~5g:250~400mL, for example, preferably 4g:280mL; the acidification temperature of carbon nanotubes is 80~100℃, for example, preferably 80℃, and the time is 3~5h, for example, preferably 3h.

[0032] It should be noted that the sulfuric acid-nitric acid mixture used in the above-mentioned acidification process of carbon nanotubes is preferably a mixture of concentrated sulfuric acid and concentrated nitric acid, and the volume ratio of the concentrated sulfuric acid to the concentrated nitric acid is preferably 3:1. Specifically, the concentrated sulfuric acid is commercially available sulfuric acid with a concentration of 98 wt%, and the concentrated nitric acid is commercially available concentrated nitric acid with a concentration of 68 wt%.

[0033] It should be noted that, in the acidification process of the carbon nanotubes described above, the mixing method of the carbon nanotubes and the sulfuric acid-nitric acid mixture is preferably ultrasonic dispersion; the ultrasonic dispersion time is preferably 1-3 hours, specifically 1 hour, 2 hours, or 3 hours. Furthermore, the temperature of the second acidification treatment is preferably 80-100°C, specifically 80°C, and the time of the second acidification treatment is preferably 3-5 hours, specifically 3 hours; the second acidification treatment is preferably carried out under conditions of water bath heating, reflux condensation, and mechanical stirring.

[0034] It should be noted that after the second acidification treatment, in this embodiment, it is also preferable to cool the obtained acidified solution to room temperature and then dilute it with deionized water, then vacuum filter and wash it until the pH of the filtrate is 6.5~7.5, preferably 7, and then dry, grind and sieve it to obtain the acidified carbon nanotubes; the drying temperature is preferably 80°C and the time is preferably 10h; the mesh size of the sieve used for grinding and sieving is 100~200 mesh, and the sieve material is collected.

[0035] In step S120, the condensing agent used in the second amidation reaction is 2-(7-azabenzotriazole)-N,N,N',N'-tetramethylurea hexafluorophosphate (HATU).

[0036] In step S120, the organic solvent used in the second amidation reaction is preferably DMF, specifically anhydrous DMF.

[0037] Further, in the second amidation reaction of step S120, the ratio of condensing agent to organic solvent is 10 mg: 100 mL. Secondly, the mass ratio of polyetherimide-grafted carbon fibers to acidified carbon nanotubes is 5-8 g: 3-5 g, more preferably 5 g: 5 g. The ratio of acidified carbon nanotubes to organic solvent is 3-5 g: 80-100 mL, more preferably 5 g: 100 mL.

[0038] Furthermore, in step S120, the temperature of the second amidation reaction is 100~120°C, for example, preferably 100°C; and the time is 10~14h, for example, preferably 12h.

[0039] It should be noted that after the second amidation reaction is completed, in this embodiment, the obtained reaction solution is preferably cooled and washed with acetone to remove excess organic solvent, and then the obtained solid product is washed with water and dried to obtain carbon nanotube-polyetherimide grafted carbon fiber; the drying temperature is preferably 80°C and the drying time is preferably 10h.

[0040] In the second amidation reaction, the unreacted amino groups of PEI on the carbon fiber surface undergo an amidation reaction with the carboxyl groups on the surface of acidified carbon nanotubes, resulting in the uniform grafting of carbon nanotubes onto the carbon fiber surface. This increases the surface roughness of the carbon fiber at the nanoscale, thereby improving the interfacial bonding strength between the carbon fiber and the nylon matrix. Simultaneously, polyetherimide contains a large number of amino groups. By grafting carbon nanotubes onto the carbon fiber surface using polyetherimide, this disclosure can increase the grafting amount of carbon nanotubes, making the carbon nanotubes uniformly dispersed on the carbon fiber surface, avoiding the aggregation of carbon nanotubes, and fully utilizing the reinforcing effect of carbon nanotubes.

[0041] S130. The carbon nanotube-polyetherimide grafted carbon fiber and nylon resin are melt-blended to obtain a carbon nanotube-polyetherimide grafted carbon fiber / nylon composite material. In step S130, the nylon resin is nylon 6.

[0042] In step S130, the mass fraction of carbon nanotube-polyetherimide grafted carbon fiber in the carbon nanotube-polyetherimide grafted carbon fiber / nylon composite material is 1wt% to 9wt%, for example, preferably 1wt%, 3wt%, 5wt%, 7wt% or 9wt%.

[0043] In step S130, the melt blending temperature is 230~250℃, the rotor speed is 40~60 rpm, for example, the temperature is preferably 235℃, the rotor speed is preferably 40 rpm, and the time is preferably 4 min.

[0044] It should be noted that the melt blending in step S130 is preferably carried out in a Brabender rheometer; before the melt blending, the nylon resin is preferably dried, and the drying temperature is preferably 80°C and the drying time is preferably 10 hours.

[0045] In this embodiment, since the polyetherimide structure contains a large number of amino groups, the amino groups on the surface of the polyetherimide-grafted carbon fiber undergo an amidation reaction with the carboxyl groups on the surface of the acidified carbon nanotubes. This not only achieves uniform dispersion of carbon nanotubes on the carbon fiber surface but also enhances the interfacial compatibility between the carbon fiber and the nylon matrix, improving the interfacial bonding strength. Secondly, by grafting carbon nanotubes to form a carbon nanotube / carbon fiber (CNT / CF) multi-scale reinforcement, multi-level reinforcement from the micron-scale (CF) to the nano-scale (CNT) is achieved, significantly improving the mechanical properties of the composite material. Furthermore, the grafting of carbon nanotubes increases the nanoscale roughness of the carbon fiber surface, improving the mechanical interlocking force between the carbon fiber and the nylon matrix, increasing the interfacial bonding strength, and further enhancing the interfacial properties of the composite material. At the same time, uniformly grafting carbon nanotubes onto the carbon fiber surface solves the problem of the difficulty in uniformly dispersing carbon nanotubes in the nylon matrix, avoids the aggregation of carbon nanotubes, and fully utilizes the reinforcing effect of carbon nanotubes. In other words, the synergistic effect of carbon nanotubes and carbon fibers effectively enhances the interfacial bonding strength between carbon nanotube-polyetherimide grafted carbon fibers and nylon, thereby improving the mechanical properties of the composite material.

[0046] In another aspect of this disclosure, a carbon nanotube-polyetherimide grafted carbon fiber / nylon composite material is proposed. The carbon nanotube-polyetherimide grafted carbon fiber / nylon composite material is prepared by the preparation method described above. For the specific process, please refer to the description above, which will not be repeated here.

[0047] It should be understood that the carbon nanotube-polyetherimide grafted carbon fiber / nylon composite material of this embodiment includes nylon resin and carbon nanotube-polyetherimide grafted carbon fiber dispersed in nylon resin, wherein the carbon nanotubes and carbon fibers in the carbon nanotube-polyetherimide grafted carbon fiber are connected by polyetherimide, the mass fraction of carbon nanotube-polyetherimide grafted carbon fiber is 1wt% to 9wt% of the composite material, and the nylon resin is preferably nylon 6.

[0048] The carbon nanotube-polyetherimide grafted carbon fiber / nylon composite material disclosed herein exhibits excellent mechanical properties, with a tensile strength reaching 105.4 MPa and a modulus reaching 2504 MPa. This composite material can be used as an external pressure reinforcement layer for marine flexible pipes and has broad application prospects.

[0049] In another aspect of this disclosure, an application of a carbon nanotube-polyetherimide grafted carbon fiber / nylon composite material is proposed, which applies the aforementioned carbon nanotube-polyetherimide grafted carbon fiber / nylon composite material to marine flexible pipes.

[0050] In this disclosure, the carbon nanotube-polyetherimide grafted carbon fiber / nylon composite material is specifically used in the external pressure reinforcement layer of a marine flexible pipe. Specifically, the marine flexible pipe comprises, from the inside out, an inner liner, an inner pressure reinforcement layer, a first isolation layer, an external pressure reinforcement layer, a second isolation layer, a tensile reinforcement layer, and an outer protective layer. The external pressure reinforcement layer employs a self-locking spiral winding structure, which enhances the external water pressure bearing capacity of the riser and resists mechanical impact loads. The carbon nanotube-polyetherimide grafted carbon fiber / nylon composite material of this disclosure exhibits excellent mechanical properties, high tensile strength and modulus, making it suitable for use as the external pressure reinforcement layer of marine flexible pipes. This disclosure does not impose special requirements on the materials of other layers in the marine flexible pipe; materials well-known to those skilled in the art can be used.

[0051] The following will further illustrate the carbon nanotube-polyetherimide grafted carbon fiber / nylon composite material and its preparation method with specific embodiments. Example 1 3g of acetone-treated carbon fiber (CF) was placed in a three-necked flask, and 50mL of concentrated nitric acid was slowly added. The mixture was heated to 80°C in a water bath and acidified for 2 hours under reflux and mechanical stirring. After cooling to room temperature, the mixture was diluted with deionized water and vacuum filtered until the pH of the filtrate was 7. The filtrate was then dried at 80°C for 10 hours to obtain acidified carbon fiber, denoted as @CF.

[0052] 1 g of PEI with a weight-average molecular weight of 1800 was dissolved in 100 mL of anhydrous DMF to prepare a 1% (w / v) solution. 5 mg of HATU and 5 g of @CF were added and mixed thoroughly. The mixture was then reacted in an oil bath at 100 °C for 12 h. The reaction solution was cooled to room temperature and washed repeatedly with acetone to remove excess DMF solvent. The resulting solid product was washed with deionized water and dried in an oven at 80 °C for 10 h to obtain PEI-grafted carbon fibers, denoted as PEI@CF.

[0053] 4g of carbon nanotubes were placed in a three-necked flask, and 210mL of concentrated sulfuric acid and 70mL of concentrated nitric acid were slowly added. The mixture was ultrasonically dispersed for 1 hour. The mixture was then heated to 80°C in a water bath and reacted for 3 hours under reflux and mechanical stirring. After cooling to room temperature, the mixture was diluted with deionized water, vacuum filtered, and repeatedly washed until the pH of the filtrate reached 7. The filtrate was dried in an oven at 80°C, ground, and sieved to obtain acidified carbon nanotubes, denoted as @CNT.

[0054] 10 mg of HATU and 5 g of @CNT were added to 100 mL of DMF and mixed thoroughly. 5 g of PEI@CF was then added, and the mixture was heated to 100 °C and reacted for 12 h. After the reaction was completed, the mixture was cooled to room temperature. The mixture was repeatedly washed with acetone to remove excess DMF solvent, washed with deionized water, and dried in an oven at 80 °C for 10 h to obtain carbon nanotube-polyetherimide grafted carbon fiber, denoted as CNT@PEI@CF.

[0055] Nylon 6 was dried in an oven at 80℃ for 10 hours. CNT@PEI@CF and nylon 6 were melt-blended in a Brabender rheometer at a temperature of 235℃, a rotor speed of 40 rpm, and a time of 4 min to prepare carbon nanotube-polyetherimide grafted carbon fiber / nylon 6 composite material. The mass fractions of CNT@PEI@CF in the carbon nanotube-polyetherimide grafted carbon fiber / nylon 6 composite material were controlled to be 1wt%, 3wt%, 5wt%, and 7wt%, respectively, and denoted as 1wt%CNT@PEI@CF / PA6, 3wt%CNT@PEI@CF / PA6, 5wt%CNT@PEI@CF / PA6, and 7wt%CNT@PEI@CF / PA6. An additional experiment without the addition of CNT@PEI@CF was set up as a control.

[0056] Figure 3 Here is a scanning electron microscope image of the surface of unmodified carbon fiber, in which... Figure 3 (a) is a 50 μm scale bar. Figure 3 (b) is a 5μm scale. According to... Figure 3 As can be seen, the surface of the unmodified carbon fiber is smooth.

[0057] Figure 4 This is a scanning electron microscope (SEM) image of the surface of carbon nanotube-polyetherimide grafted carbon fibers, in which... Figure 4 (a) is a 50 μm scale bar. Figure 4 (b) is a 5μm scale. According to... Figure 4 It can be seen that carbon nanotubes are grafted onto the surface of the carbon fiber, and the successful grafting of carbon nanotubes increases the surface roughness of the carbon fiber at the nanoscale.

[0058] The specific tensile strength and modulus of the carbon nanotube-polyetherimide grafted carbon fiber / nylon 6 composite material are shown in Table 1.

[0059] As shown in Table 1, the tensile strength and modulus of the composite material without CNT@PEI@CF are 65.7 MPa and 1168 MPa, respectively. The tensile strength and modulus of the composite material with 1 wt% CNT@PEI@CF / PA6 are 70.3 MPa and 1385 MPa, respectively. The tensile strength and modulus of the composite material with 3 wt% CNT@PEI@CF / PA6 are 85.5 MPa and 1868 MPa, respectively. The tensile strength and modulus of the composite material with 5 wt% CNT@PEI@CF / PA6 are 102.1 MPa and 2117 MPa, respectively. The tensile strength and modulus of the composite material with 7 wt% CNT@PEI@CF / PA6 are 105.4 MPa and 2504 MPa, respectively. It can be seen that the tensile strength and modulus of the composite material with different CNT@PEI@CF contents are significantly improved compared with Nylon 6.

[0060] Table 1. Tensile strength and modulus of CNT@PEI@CF / PA6 composites with different contents

[0061] Comparative Example 1 Nylon 6 was dried in an oven at 80℃ for 10 hours. Carbon fiber (CF) and nylon 6 were melt-blended in a Brabender rheometer at a temperature of 235℃, a rotor speed of 40 rpm, and a time of 4 min to prepare a carbon fiber / nylon 6 composite material. The mass fraction of carbon fiber in the composite material was controlled to be 5 wt%, denoted as 5 wt% CF / PA6.

[0062] According to Table 2, the tensile strength of the product with 5wt% CF / PA6 is 78.3MPa and the modulus is 1755MPa.

[0063] Comparative Example 2 Nylon 6 was dried in an oven at 80°C for 10 hours. The acidified carbon fiber (@CF) prepared in Example 1 was melt-blended with nylon 6 in a Brabender rheometer at a temperature of 235°C, a rotor speed of 40 rpm, and a time of 4 minutes to prepare the acidified carbon fiber / nylon 6 composite material. The mass fraction of @CF in the composite material was controlled to be 5 wt%, denoted as 5 wt% @CF / PA6.

[0064] According to Table 2, the tensile strength of CF / PA6 with an added content of 5wt% is 83.8MPa and the modulus is 1829MPa.

[0065] Comparative Example 3 Weigh 3g of acidified carbon fiber (preparation method is the same as in Example 1) and 4g of KH550, add 25mL of deionized water and 235mL of anhydrous ethanol, mix well, react in a water bath at 80℃ for 6h, wash at least 3 times with anhydrous ethanol, and dry in a forced-air dryer at 80℃ for 10h to obtain KH550 grafted carbon fiber, denoted as KH550@CF. The reaction process of KH550 and acidified carbon fiber is shown in the figure. Figure 5 As shown.

[0066] Nylon 6 was dried in an oven at 80℃ for 10 hours. KH550@CF and nylon 6 were melt-blended in a Brabender rheometer at a temperature of 235℃, a rotor speed of 40 rpm, and a time of 4 min to prepare a KH550 grafted carbon fiber / nylon 6 composite material. The mass fraction of KH550@CF in the composite material was controlled to be 5wt%, denoted as 5wt%KH550@CF / PA6.

[0067] According to Table 2, the tensile strength of KH550@CF / PA6 with an added content of 5wt% is 90.8MPa and the modulus is 1901MPa.

[0068] Comparative Example 4 Nylon 6 was dried in an oven at 80°C for 10 hours. The PEI-grafted carbon fiber (PEI@CF) prepared in Example 1 was melt-blended with nylon 6 in a Brabender rheometer at a temperature of 235°C, a rotor speed of 40 rpm, and a time of 4 min to prepare a PEI-grafted carbon fiber / nylon 6 composite material. The mass fraction of PEI@CF in the composite material was controlled to be 5 wt%, which was denoted as 5 wt% PEI@CF / PA6.

[0069] According to Table 2, the tensile strength of PEI@CF / PA6 with an added content of 5wt% is 94.6MPa and the modulus is 1906MPa.

[0070] Table 2 Tensile strength and modulus of different composite materials

[0071] In summary, the CNT@PEI@CF composite material exhibits relatively high tensile strength and modulus compared to other materials, indicating that the modification effect of simple carbon fiber or acidified carbon fiber is limited. Through a double amidation reaction mediated by polyethyleneimine (PEI), covalent bonding networks are constructed on the surfaces of carbon fiber (CF) and carbon nanotubes (CNTs), forming a "carbon fiber-PEI-carbon nanotube" chemical bond link. This promotes the formation of a nanoscale rough structure of CNTs on the CF surface. On the one hand, this enhances the interfacial bonding with the nylon matrix through mechanical interlocking; on the other hand, the molecular bridging effect of PEI achieves uniform dispersion of CNTs on the CF surface, and subsequently, uniform dispersion within the nylon matrix. Therefore, the method of this invention for modifying carbon fiber can significantly improve the compatibility and interfacial bonding performance between carbon fiber and nylon, thereby greatly improving the mechanical properties of the composite material. The resulting composite material has high tensile strength and modulus, making it suitable for use as an external pressure reinforcement layer in marine flexible pipes. This solves the technical bottlenecks of insufficient interfacial bonding strength and carbon nanotube agglomeration in traditional carbon fiber modification, synergistically improving the overall mechanical properties of the composite material from two dimensions: interfacial strengthening and filler dispersion.

[0072] This disclosure presents a carbon nanotube-polyetherimide grafted carbon fiber / nylon composite material, its preparation method, and its application, which have the following advantages compared to the prior art: This disclosure utilizes the amidation reaction between the amino groups on the surface of polyetherimide-grafted carbon fibers and the carboxyl groups on the surface of acidified carbon nanotubes. This not only achieves uniform dispersion of carbon nanotubes on the carbon fiber surface but also enhances the interfacial compatibility between carbon fibers and the nylon matrix, improving the interfacial bonding strength. By grafting carbon nanotubes to form a carbon nanotube / carbon fiber (CNT / CF) multi-scale reinforcement, multi-level reinforcement from the micron-scale (CF) to the nano-scale (CNT) is achieved, significantly improving the mechanical properties of the composite material. The grafting of carbon nanotubes increases the nanoscale roughness of the carbon fiber surface, improving the mechanical interlocking force between the carbon fiber and the nylon matrix, increasing the interfacial bonding strength, and further enhancing the interfacial properties of the composite material. Simultaneously, uniformly grafting carbon nanotubes onto the carbon fiber surface solves the problem of the difficulty in uniformly dispersing carbon nanotubes in the nylon matrix, avoids the aggregation of carbon nanotubes, and fully utilizes the reinforcing effect of carbon nanotubes.

[0073] It is understood that the above embodiments are merely exemplary implementations used to illustrate the principles of this disclosure, and this disclosure is not limited thereto. For those skilled in the art, various modifications can be made without departing from the spirit and substance of this disclosure, and these modifications are also considered to be within the scope of protection of this disclosure.

Claims

1. A method for preparing a carbon nanotube-polyetherimide grafted carbon fiber / nylon composite material, characterized in that, The preparation method includes: Polyetherimide, condensing agent, acidified carbon fiber and organic solvent are mixed and subjected to a first amidation reaction to obtain polyetherimide grafted carbon fiber; The polyetherimide-grafted carbon fibers, condensing agent, acidified carbon nanotubes and organic solvent are mixed and subjected to a second amidation reaction to obtain carbon nanotube-polyetherimide-grafted carbon fibers. The carbon nanotube-polyetherimide grafted carbon fiber and nylon resin are melt-blended to obtain a carbon nanotube-polyetherimide grafted carbon fiber / nylon composite material.

2. The preparation method according to claim 1, characterized in that, The acidified carbon fiber is formed using the following method: Carbon fibers are mixed with nitric acid and then acidified to obtain acidified carbon fibers; wherein... The acidification treatment was carried out at a temperature of 80°C for 2 hours.

3. The preparation method according to claim 1, characterized in that, In the first amidation reaction, the ratio of condensing agent to organic solvent is 5 mg: 100 mL, the mass ratio of polyetherimide to acidified carbon fiber is 1 g: 5 g, and the ratio of polyetherimide to organic solvent is 1 g: 100 mL. The temperature of the first amidation reaction was 100℃, and the reaction time was 12h.

4. The preparation method according to claim 1, characterized in that, The acidified carbon nanotubes are formed using the following method: Carbon nanotubes are mixed with a sulfuric acid-nitric acid mixture and then acidified to obtain acidified carbon nanotubes; among which... The ratio of carbon nanotubes to sulfuric acid-nitric acid mixture is 4g:280mL; The acidification treatment was carried out at a temperature of 80°C for 3 hours.

5. The preparation method according to claim 1, characterized in that, In the second amidation reaction, the ratio of condensing agent to organic solvent is 10 mg: 100 mL, the mass ratio of polyetherimide grafted carbon fiber to acidified carbon nanotube is 5 g: 5 g, and the ratio of acidified carbon nanotube to organic solvent is 5 g: 100 mL. The second amidation reaction was carried out at 100°C for 12 hours.

6. The preparation method according to any one of claims 1 to 5, characterized in that, The condensing agent is 2-(7-azabenzotriazole)-N,N,N',N'-tetramethylurea hexafluorophosphate; The polyetherimide has a weight-average molecular weight of 1800; The nylon resin is nylon 6.

7. The preparation method according to any one of claims 1 to 5, characterized in that, The melt blending temperature was 235°C, the rotor speed was 40 rpm, and the time was 4 min.

8. The preparation method according to any one of claims 1 to 5, characterized in that, The mass fraction of carbon nanotube-polyetherimide grafted carbon fiber / nylon composite material is 1wt%~7wt%.

9. A carbon nanotube-polyetherimide grafted carbon fiber / nylon composite material, characterized in that, The carbon nanotube-polyetherimide grafted carbon fiber / nylon composite material is prepared by the preparation method described in any one of claims 1 to 8.

10. An application of a carbon nanotube-polyetherimide grafted carbon fiber / nylon composite material, characterized in that, The carbon nanotube-polyetherimide grafted carbon fiber / nylon composite material described in claim 9 is used in marine flexible pipes.

Citation Information

Cited By

  • Modified carbon felt reinforced fiber resin-based composite material as well as preparation method and application thereof

    CN122060194A